Development of Methods for Selecting Respiratory Dust Protection for Miners - N. M., Akhmedova; Kh. T., Rabbimov (European Journal of Life Safety and Stability (2660-9630), 2022)
The article discusses the main trends in dust entry into the atmosphere of quarries, depending on air and soil humidity, the amount of precipitation, wind speed, the number and duration of calm periods and near-surface inversions of the quarry location area, which will determine the dust load on the environment and on the body of miners, as well as the development of methods for choosing means of protection against dust from the respiratory organs of miners.